1987
DOI: 10.1103/physrevd.36.3138
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of the Yang-Mills theories in the light-cone gauge

Abstract: The structure of the renormalization of the Yang-Mills theories in the light-cone gauge is investigated. It is shown that, despite the appearance of an infinite number of nonlocal divergent terms, the theory can be made finite to any order in the loop expansion by introducing a finite number of renormalization constants. Those constants can be interpreted as coefficients of a canonical transformation of fields and coupling constants in such a way that gauge invariance and unitarity of the renormalized theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 26 publications
3
69
0
Order By: Relevance
“…Though we are aware of the fact that due to the heavy quark field our operators are in no representation of the conformal group we use the same notation as in [18]. The ⊗ just indicates that the fields have open colour indices so that 21) where the generators of the SU (3) have to be taken in the appropriate representation:…”
Section: Heavy-light Light Ray Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though we are aware of the fact that due to the heavy quark field our operators are in no representation of the conformal group we use the same notation as in [18]. The ⊗ just indicates that the fields have open colour indices so that 21) where the generators of the SU (3) have to be taken in the appropriate representation:…”
Section: Heavy-light Light Ray Operatorsmentioning
confidence: 99%
“…A drawback of using the light cone gauge is the explicit breaking of Lorentz invariance so that plus and minus components of the fields renormalise differently [21] […”
Section: Renormalisation Group Equations and Light Cone Gaugementioning
confidence: 99%
“…What happens, as we shall here explicitely show up to the one loop order, is that in dimensionally regularized truncated Green's functions all those non-covariant terms cancel, leaving us with the very same renormalizable one loop structures, as found in the standard STC framework [8].…”
Section: Light-front Qed In the Light-cone Temporal Gaugementioning
confidence: 54%
“…as independent fields, a straightforward although very tedious calculation leads to the following result: namely, 8) where, once again, we have denoted the Dirac's brackets matrix as…”
Section: Light-front Qed In the Light-cone Temporal Gaugementioning
confidence: 99%
“…Bassetto, et al have given a derivation of the ML propagator in the framework of equal-time quantization [5], and have further shown that gauge theories defined in this way are renormalizable [6] (although nonlocal counterterms are necessary to render offshell Green functions finite). A central feature of their construction is that they do not reduce down to the physical (transverse) degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%